Security for mobility - Mitchell, Chris 1953- (IET telecommunications series, 2004)
Over the last decade, mobile telecommunications has grown dramatically from a niche technology to a massive industry. As the mobile phone becomes ubiquitous and the divisions between PCs, personal digital assistants, mobile phones and other mobile devices becomes blurred, the security both of the information handled by these devices and the devices themselves becomes increasingly important. The book consists of 17 chapters covering current developments in security for mobility; underlying technologies; network security; mobile code issues; application security; and the future.